Clinical group and modified TNM stage for rhabdomyosarcoma: A review from the Children's Oncology Group. Issue 6 (6th March 2022) - Crane, Jacquelyn N.; Xue, Wei; Qumseya, Amira; Gao, Zhengya; Arndt, Carola A. S.; Donaldson, Sarah S.; Harrison, Douglas J.; Hawkins, Douglas S.; Linardic, Corinne M.; Mascarenhas, Leo; Meyer, William H.; Rodeberg, David A.; et al.
Abstract: The Children's Oncology Group (COG) uses Clinical Group (CG) and modified Tumor Node Metastasis (TNM) stage to classify rhabdomyosarcoma (RMS). CG is based on surgicopathologic findings and is determined after the completion of initial surgical procedure(s) but prior to chemotherapy and/or radiation therapy. The modified TNM stage is based on clinical and radiographic findings and is assigned prior to any treatment. These systems have evolved over several decades. We review the history, evolution, and rationale behind the current CG and modified TNM classification systems used by COG for RMS. Data from the seven most recently completed and reported frontline COG trials (D9602, D9802, D9803, ARST0331, ARST0431, ARST0531, ARST08P1) were analyzed, and confirm that CG and modified TNM stage remain relevant and useful for predicting prognosis in RMS. We propose updates based on recent data and discuss factors warranting future study to further optimize these classification systems.